2005
DOI: 10.1093/pcp/pci122
|View full text |Cite
|
Sign up to set email alerts
|

Volatile C6-aldehydes and Allo-ocimene Activate Defense Genes and Induce Resistance against Botrytis cinerea in Arabidopsis thaliana

Abstract: Green leafy volatiles or isoprenoids are produced after mechanical wounding or pathogen/herbivore attacks in higher plants. We monitored expression profiles of the genes involved in defense responses upon exposing Arabidopsis thaliana to the volatiles. Among the genes investigated, those known to be induced by mechanical wounding and/or jasmonate application, such as chalcone synthase (CHS), caffeic acid-O-methyltransferase (COMT), diacylglycerol kinase1 (DGK1), glutathione-S-transferase1 (GST1) and lipoxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
193
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(205 citation statements)
references
References 45 publications
4
193
0
2
Order By: Relevance
“…Which VOCs, then, were responsible for the responses that we observed? Green-leaf volatiles have repeatedly been reported to be active in airborne induction of herbivore resistance (Engelberth et al, 2004;Farag et al, 2005;Ruther and Kleier, 2005;Mirabella et al, 2008), and they can also enhance a plant's direct resistance to certain pathogens, particularly necrotrophic fungi (Kishimoto et al, 2005;Matsui, 2006;Shiojiri et al, 2006). Certain volatiles even might be involved in the resistance of plants to abiotic stress (Behnke et al, 2007), and BTH treatment has been reported to enhance the attractiveness of herbivore-damaged corn seedlings to parasitic wasps (Rostás and Turlings, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which VOCs, then, were responsible for the responses that we observed? Green-leaf volatiles have repeatedly been reported to be active in airborne induction of herbivore resistance (Engelberth et al, 2004;Farag et al, 2005;Ruther and Kleier, 2005;Mirabella et al, 2008), and they can also enhance a plant's direct resistance to certain pathogens, particularly necrotrophic fungi (Kishimoto et al, 2005;Matsui, 2006;Shiojiri et al, 2006). Certain volatiles even might be involved in the resistance of plants to abiotic stress (Behnke et al, 2007), and BTH treatment has been reported to enhance the attractiveness of herbivore-damaged corn seedlings to parasitic wasps (Rostás and Turlings, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exposure to VOCs such as trans-2-hexenal, cis-3-hexenal, or cis-3-hexenol enhanced resistance of Arabidopsis against the fungal pathogen Botrytis cinerea (Kishimoto et al, 2005), which indicates that VOCs may also induce disease resistance. However, the wound response, the induction of VOCs, the effects of plant growth-promoting rhizobacteria, and even the resistance to necrotrophic pathogens such as B. cinerea and Alternaria brassiccicola are mediated via JA signaling (Wasternack and Parthier, 1997;Pieterse et al, 1998;Schilmiller and Howe, 2005;Francia et al, 2007;Heil, 2008;Heil and Ton, 2008).…”
mentioning
confidence: 99%
“…The (3Z)-hexenal and 12-oxo-cis-dodecenoic acid formed by 13-HPL have the capability to isomerize non-enzymatically (43) or by the isomerases (44,45) to biologically active forms, 2E-hexenal and 12-oxo-trans-dodecenoic acid (also known as traumatin), respectively. Traumatin plays an important role in plant wound healing (46), and 2(E)-hexenal induces the expression of HPL, AOS, LOX (47,48), and other stress genes in plants (49). Moreover, the electrophilic ␣,␤-unsaturated carbonyl group of aldehydes might interact with nucleophiles in biological systems (50,51), and in plants, antimicrobial properties of oxylipins including 2(E)-hexenal have been presented by Prost et al (52).…”
Section: Discussionmentioning
confidence: 99%
“…There are few possible interpretations of this apparent lack of enhancement of the cHPL-LOX activity; (i) in contrast to its plant counterpart, the cHPL may not be involved in a response to mechanical injury, and (ii) given that plant oxylipin synthesis is activated within seconds or a few minutes of wounding (54,55), a short-lived increase in the cHPL-LOX products may occur immediately after wounding, which has not been analyzed (16,53). Activation of the plant HPL pathway is associated with changes in the expression of other defense genes (47,49,56), and equivalent experiments to explore effects of the coral lyase products are required to elucidate the role of cHPL-LOX pathway.…”
Section: Discussionmentioning
confidence: 99%
“…1 Terpenoids are a class of volatile secondary compounds that fulfill many ecological roles in plants interacting with their biotic environment, including pollinator attraction, direct and indirect defense against insects, bacteria, fungi and even mammals, 2 as well as in intraand inter-plant signaling. 3,4 Terpenes are produced from a small number of simple prenyl diphosphate substrates, but terpene synthase (TPS) enzymes are capable of producing many terpene skeletons. 2 Complexity is further increased by the action of several modifying enzymes leading to the production of even larger numbers of volatile secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%